# Simplify: 1/(x-y)(x-z) + 1/(y-z)(x-z)I thought it wass a partial fraction. However, it is not since the second denominator has no x, (y-z).

*print*Print*list*Cite

### 1 Answer

`1/((x-y)(x-z)) + 1/((y-z)(x-z))`

Find the lowest common denominator (LCD): (x-y)(x-z)(y-z)

Apply the LCD to each part of the fraction:

= ``

Remove the brackets from the numerator:

= ``

The 'y' will cancel out from the numerator

= ``

Rearrange the numerator:

= ``

The (x-z) from the numerator cross cancels with the denominator

= `1/((x-y)(y-z))`

**= 1/(x-y)(y-z)**